Principios curriculares de un programa de residentes como docentes: una aproximación desde las revisiones sistemáticas - Villamizar-Gomez, Licet; Casanova-Libreros, Rosangela; Ibáñez-Antequera, Claudia (Spanish Journal of Medical Education, 2021)
Background. Part of the teaching-learning in medical residences is generated with the residence partners; Programs of resident- as-teachers (PRAT) strengthen this pedagogical practice. Objectives. To analyze curricular principles of a PRAT according to Tyler's posture and to identify educational strategies that change behavior in resident learning and educational organization according to Kirkpatrick model. Methods. A review of systematic reviews was conducted in MEDLINE, EMBASE, ERIC, EPISTEMONIKOS, The Cochrane Database of Systematic Reviews and LILACS. The overall quality was evaluated using the AMSTAR tool. Through the published literature, Tyler's curriculum posture was answered by describing educational strategies, their evaluation and impact of evaluation according to Kirkpatrick. Results. Seven systematic reviews were included; one of them obtained high methodological quality. According to the literature, a PRAT requires continuous evaluation of its participants. The most used educational strategies were the workshop and the seminar. Topics that can be included in PRAT are leadership, bedside teaching skills, evaluation, and feedback. In practice, pedagogical activities similar to One-minute preceptor can be encouraged. The monitoring of the PRCD requires direct observation through OSTE (Objective Structured Teaching Exercises). Conclusions. The PRAT aims to generate teaching moments that feed the reflection of pedagogical practice. The PRAT must have educational strategies that increase confidence in teaching, pedagogical skills, and valid assessments of teaching practice.